Pan młody i przymierze oblubieńczej miłości (Mk 2,18-22) - Bartosz Adamczewski (Verbum Vitae, 2003)
Fragment Mk 2:18-22 consists of two originally separate units: Mk 2:18-20 and 2:20-21. Each of them plays on the OT idea of covenant, which has not been broken by human sins, but is freshly renewed by merciful God. The new covenant of spousal love established in Jesus is not only an accomplished fact, but also always a challenge and invitation to seek Jesus - physically absent, but spiritually present for His people.